UJI KETAHANAN EMPAT VARIETAS TANAMAN JAGUNG TERHADAP WERENG Stenocranus pacificus Kirkaldy (Hemiptera: Delphacidae) DENGAN MENGGUNAKAN PERANGKAP WARNA BERPEREKAT DI KECAMATAN KUTALIMBARU KABUPATEN DELI SERDANG - Putri Murdianti (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
Observation of maize varieties resistance is the beginning to determine the level of resistance of each maize variety against of corn planthopper S. pacificus attacks and also to determine the most effective color trap used. This research was carried out in a corn farm in Suka Rende Village, Kutalimbaru District, Deli Serdang Regency (500 meters above sea level) from July to November 2018. The research used a Separate Plot Design with the main plot being varieties (Bioseed 54, Bisi 18, Pioneer 32 , and Local) and subplots are color traps (white, yellow, blue, green). The results showed that the Bioseed 54 variety had a low level of resistance to corn planthopper S. pacificus attacks. The yellow color is the color preferred by S. pacificus planthoppers.